"De tycka emellertid av gammal vana att det smakar gott, och tro dessutom att det är bra för hälsan" - Qvarnström, Elin (2007)
Meat and fish was the most important food for the Sami people in northern Scandinavia until the beginning of the 20th century. It is not so well known that the Sami people also used a lot of wild plants as food and medicine although that kind of food was relatively common among them until the end of the 19th century. The purpose of this master thesis has been to describe which plants the Sami people used in general and also which plants were the most commonly used, and when and how these plants were harvested. I also wanted to measure the quantities of Angelica archangelica and Rumex acestosa within traditional harvest sites. Furthermore I wanted to find out if the plant use differed among Sami groups geographically. My last issue was to find out if there were any similarities between the Sami people and other circumpolar people's when it comes to plant use. For this purpose I have used old and new literature, ethnological material, field studies and interviews. According to my studies (and other research) it seems like the Angelica archangelica has been the most valuable and most used plant among the Sami people. The causes for that can be the fact that the plant is easy to use and vary. The whole plant is usable and it has also been used as a medicine. It is also easy to harvest the plant. The Angelica was also valuable because boiled stalks could be mixed with reindeer milk, which preserved the milk. One could also dry the plant. This made it possible for the Sami people to have plant food year-round. It is possible that the Sami people have cultivated the Angelica (since they also harvested the flowers were all the seeds were it could have led to a shortage of the plant). If they cultivated Angelica that made it easier for them to have the plant more close to their homes and also to get greater amounts of the Angelica. Pine bark was another important plant for the Sami people. It was possible to dry the bark and therefore that plant could also be preserved yearround. I have not found anything particular that ...